Equity In Construction Law – New Malaysian Directions: The Radio & General Trading Co. Sdn Bhd V Wayss & Freytag (M) Sdn Bhd - Melnnis, J. Arthur (Journal of Malaysian and Comparative Law, 2000)
As the title of this paper indicates, I wanted to look briefly at the role of equity in Malaysian construction cases. Alas it was both encouraging and discouraging to quickly come to see that the topic was larger than I had anticipated. Some choices clearly had to be made. Thus, in the end, I have perused a selection of recent cases to come up with one case that is at once interesting and ilustrative of new Malaysian directions.